#### Answer

y=-3x+18

#### Work Step by Step

m=-3
y-y$_1$=m(x-x$_1$)
y-6=-3(x-4)
y=-3x+12+6
y=-3x+18

Published by
Brooks Cole

ISBN 10:
0-53449-636-9

ISBN 13:
978-0-53449-636-4

y=-3x+18

m=-3
y-y$_1$=m(x-x$_1$)
y-6=-3(x-4)
y=-3x+12+6
y=-3x+18

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.